Having a Usual Source of Care Is Associated with Longer Telomere Length in a National Sample of Older Adults - Baltrus, Peter T. (J Am Board Fam Med, 2020)
OBJECTIVE: To provide a potential biological, mechanistic link for the well-established association between primary care access and reduced mortality, this study sought to measure the impact of having a usual source of health care on leukocyte telomere length (LTL). DATA SOURCES: Our study population included 3202 participants aged 50 to 84 years from National Health and Nutrition Examination Survey 1999 to 2001. STUDY DESIGN: Cross-sectional Study. LTLs between people with and without a usual source of care were compared using unadjusted and adjusted linear regression models. Fully adjusted models accounted for demographic characteristics, health conditions, and health behaviors. PRINCIPAL FINDINGS: After controlling for individual factors, health conditions, and health behaviors, people who had a usual source of health care had significantly longer LTL (β = 89.8 base pairs, P-value = .005) compared with those without a usual source of care; corresponding to approximately 7 years of life. CONCLUSIONS: Having a usual source of health care is associated with longer LTL among older adults. This study provides a potential biologic link for the noted association between primary care access and reduced mortality that has been observed at the individual and population level.